Maternal Allopurinol Prevents Cardiac Dysfunction in Adult Male Offspring Programmed by Chronic Hypoxia During Pregnancy. Issue 4 (October 2018) - Niu, Youguo; Kane, Andrew D.; Lusby, Ciara M.; Allison, Beth J.; Chua, Yi Yi; Kaandorp, Joepe J.; Nevin-Dolan, Rhiannon; Ashmore, Thomas J.; Blackmore, Heather L.; Derks, Jan B.; Ozanne, Susan E.; Giussani, Dino A.
Abstract : Integrating functional and molecular levels, we investigated the effects of maternal treatment with a xanthine oxidase inhibitor on the programming of cardiac dysfunction in adult offspring using an established rat model of hypoxic pregnancy. Female Wistar rats were divided into normoxic or hypoxic (13% O2 ) pregnancy±maternal allopurinol treatment (30 mg kg -1 d -1 ). At 4 months, hearts were isolated from 1 male per litter per outcome variable to determine cardiac function and responses to ischemia-reperfusion in a Langendorff preparation. Sympathetic dominance, perfusate CK (creatine kinase) and LDH (lactate dehydrogenase) and the cardiac protein expression of the β1 -adrenergic receptor, the M2 Ach receptor (muscarinic type-2 acetylcholine receptor), and the SERCA2a (sarcoplasmic reticulum Ca 2+ ATPase 2a) were determined. Relative to controls, offspring from hypoxic pregnancy showed elevated left ventricular end diastolic pressure (+34.7%), enhanced contractility (dP/dtmax, +41.6%), reduced coronary flow rate (−21%) and an impaired recovery to ischemia-reperfusion (left ventricular diastolic pressure, area under the curve recovery −19.1%; all P <0.05). Increased sympathetic reactivity (heart rate, +755.5%; left ventricular diastolic pressure, +418.9%) contributed to the enhanced myocardial contractility ( P <0.05). Perfusate CK (+431%) and LDH (+251.3%) and the cardiac expression of SERCA2a (+71.4%) were also elevated ( P <0.05), further linking molecular markers of cardiac stress and injury to dysfunction. Maternal allopurinol restored all functional and molecular indices of cardiac pathology. The data support a link between xanthine oxidase–derived oxidative stress in hypoxic pregnancy and cardiac dysfunction in the adult offspring, providing a target for early intervention in the developmental programming of heart disease. Abstract : Supplemental Digital Content is available in the text.